2007
DOI: 10.1038/sj.npp.1301386
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone Repairs Region-Dependent Alteration of Synapsin I in Hippocampus in Rat Model of Depression

Abstract: Clinical investigations present much evidence that the glucocorticoid receptor (GR) antagonist mifepristone leads to a rapid amelioration of depression. The molecular mechanisms of mifepristone involved in the treatment of depression are not fully understood. Depression is associated with hippocampal plasticity, for which increased excitatory amino acid (EAA) release in CA3 induced by chronic stress is responsible, and glucocorticoids have a permissive role and act synergistically with EAAs in producing neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 51 publications
9
49
0
Order By: Relevance
“…Whether mifepristone's prevention and/or reversal of the disturbances caused by diabetes is directly on hippocampal astrocytes, neurons, and proliferative cells, or by changing its surroundings (ie their inputs) requires further investigation. It is worth noting that 4 days mifepristone treatment can affect not only the functioning of these cells (present study, Karst and Joëls, 2007;Wu et al, 2007;Mayer et al, 2006;Wong and Herbert, 2005), but also the innervating projections from other brain regions (Witter, 2007). Moreover, in the present study, we reported that reversion of hippocampal alterations takes place in the face of hypercorticism.…”
Section: Mifepristone In Stz-diabetic Mice Y Revsin Et Alsupporting
confidence: 54%
“…Whether mifepristone's prevention and/or reversal of the disturbances caused by diabetes is directly on hippocampal astrocytes, neurons, and proliferative cells, or by changing its surroundings (ie their inputs) requires further investigation. It is worth noting that 4 days mifepristone treatment can affect not only the functioning of these cells (present study, Karst and Joëls, 2007;Wu et al, 2007;Mayer et al, 2006;Wong and Herbert, 2005), but also the innervating projections from other brain regions (Witter, 2007). Moreover, in the present study, we reported that reversion of hippocampal alterations takes place in the face of hypercorticism.…”
Section: Mifepristone In Stz-diabetic Mice Y Revsin Et Alsupporting
confidence: 54%
“…32 The necessity of corticosterone in CMS-induced depression is further demonstrated by the lack of depressive symptoms in adrenalectomized mice. This finding, together with the results of a recent study demonstrating that administration of the glucocorticoid receptor antagonist mifepristone (RU-486) abolished CMS-induced behavioral and neural alterations, 67 indicate that at least in the CMS model, glucocorticoids secretion is causally related to the development of the depressive symptoms. This conclusion is further strengthened by the finding that chronic corticosterone administration resulted in depressive symptoms similar to those displayed by mice that were exposed to CMS.…”
Section: Discussionmentioning
confidence: 83%
“…In parallel, chronic treatment with ESC, as well as with HG, at 5 mg/kg ameliorated the anxiety/ depression-like behaviors caused by UCMS exposure, including increase of locomotor activity in the OFT, percentage of time spent in open arm in the EPM to some extent. Anhedonia, one of the core symptoms of depression, has been defined as decreased responsiveness to rewards, which was measured in depressive animals by decreased preference of sucrose solution (Willner, 1997;Willner et al, 1987;Wu et al, 2007). The depressive state induced by UCMS is associated with anhedonia and despairing behaviors that can be assessed in the SPT and FST, respectively.…”
Section: Discussionmentioning
confidence: 99%